The Faktor-Faktor Yang Memengaruhi Audit Delay Ditinjau Dari Ukuran Perusahaan, Solvabilitas, dan Opini Audit - Nia Fidia Astuti; Yovita Ariani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to ascertain and analyze the impact of Firm size, solvency, and audit opinion on audit delay across various industries of companies listed on the Indonesia Stock Exchange during the period from 2018 to 2022, which were delayed in publishing their financial reports. The research methodology employed is quantitative, utilizing secondary data from financial reports as the primary data source. The research sample was selected using a nonprobability sampling method, specifically employing the purposive sampling technique, resulting in the inclusion of 28 companies with a total of 140 data observations. Subsequently, outlier analysis was performed on three companies, resulting in a final research dataset of 125 data observations..The technique employed in this research is a multiple linear regression analysis. Based on the results of the research, the partial test (t-test) indicates that the Firm size and solvency do not significantly influence audit delay, with significance values for each variable being 0.110 and 0.483, respectively, both greater than 0.05. On the other hand, audit opinion significantly affects audit delay with a significance value of 0, which is less than or equal to 0.05. The simultaneous test (f-test) concludes that the variables of Company size, solvency, and audit opinion collectively have a significant impact on audit delay, with a significance value of 0.